KAYEA Wall, and MESUA L. (Guttiferae) - a. j. g. h. kostermans (REINWARDTIA, 1969)
Kayea Wallich, PI. As. rar. 3: 5. 1832 and Mesua L., Spec. PI. 515.1753 are very closely related.Bentham and Hooker (Gen. PI. 1: 176. 1862) distinguished both generain this way, that Kayea has a one-celled ovarium with one seed and a4-fid style, whereas Mesua has a 2-celled ovary and 4 ovules, the stigmabeing peltate.